Tingkat Partisipasi Masyarakat dalam Pengelolaan Tanaman Kemiri (Aleurites moluccana) di Kelompok Pengelola Hutan Kemasyarakatan (HKm) Tuar Tana Desa Hikong Kecamatan Talibura Kabupaten Sikka - Mario Fernando Eni Embu; Nixon Rammang; Pamona Silvia Sinaga (Wana Lestari, 2025)
Candlenut (Aleurites moluccana) is one of the leading non-timber forest product (NTFP) commodities in East Nusa Tenggara, possessing high economic value and substantial potential as a livelihood source for communities living around forests. This study aims to determine the level of community participation in candlenut (Aleurites moluccana) management within the Tuar Tana HKm Management Group in Hikong Village, Talibura District, Sikka Regency. The research was conducted in October 2024 using a quantitative descriptive method with a field survey approach. Primary data were collected through questionnaires developed based on participation indicators and distributed to 38 respondents selected using purposive sampling. The collected data were analyzed using a Likert scale to measure participation levels across four management stages: planning, implementation, benefit utilization, and evaluation. The results showed that the overall community participation level was categorized as high. In the planning stage, participation reached 68.21%, reflecting involvement in work plan formulation despite constraints from relatively low education levels. The implementation stage scored 72.96%, indicating active roles in land preparation, planting, and maintenance. In the benefit utilization stage, participation reached 68.12%, representing engagement in processing and marketing harvest products despite limited market access. The evaluation stage scored 63.15%, showing contributions to assessing program success, though feedback provision remains suboptimal. Factors driving participation included productive age, farming experience, and economic motivation, while the main constraints were limited facilities, infrastructure, and education levels.